Anisotropy of silicon surface energy - Yurov, V.M. (Recent Contributions to Physics, 2021)
An empirical model of a metal surface layer is proposed, consisting of layers R0, R(I), R(II), R∞. The R0 layer is called the de Broglie layer R0 = λдБ = ћ/p and for metals ranges from 0.01 nm to 0.1 nm. Quantum dimensional effects begin in this layer. The size effects in the R(I) layer are determined by the entire collective of atoms in the system (collective processes). Such "quasi-classical" size effects are observed only in nanostructures and for metals they range from 1 nm to 7 nm. The R(II) layer extends approximately to the size R(II) ≈9R = R∞ (<100 nm), where the bulk phase begins. The R (II) layer should have many dimensional effects associated with optics, magnetism, and other physical properties. The Rusanov A.I. equation relating the surface energy to the particle size is valid only in the R(I) layer. Taking this equation into account in our model leads to anisotropy of the metal crystal lattice. In the work of Shebzukhova and Aref’eva, by the method of electronic-statistical calculation of the anisotropy of the surface energy of metals, a method was determined for the work function of electrons from a metal. In Bokarev’s work, the anisotropy of the surface energy of single crystals was calculated from the model of coordination melting of crystals. In our proposed empirical model, not only the anisotropy is calculated, but also the thickness of the surface layer for porous silicon. Key words: porous silicon, surface layer, atomic volume, nanostructure